Culture and Tourism in Porto City Centre: Conflicts and (Im)Possible Solutions - Gusman, Inês (2019)
City centres are spaces where different economic and cultural values converge as a consequence of their current uses and functions. In the case of Porto (Portugal), more than 20 years after being declared a World Heritage Site by UNESCO (in 1996), tourism has had remarkable effects on its physical, social and economic features. Therefore, Porto—and in particular its city centre—is taken in this article as the object of study. The interest of this space lies in the fact that it has been rapidly transformed from a devalued old area into the centre of an important urban tourism destination on a European level. Based on the spatial and temporal analysis of a set of indicators related to tourism, housing and economic activity, we identify the main threats that this “culture-led regeneration”—much supported by tourism—could have on the cultural values of Porto. Our results show that this process is promoting an excessive use of space by tourism and an overexploitation of cultural values. We conclude with some policy recommendations to support strategies capable of keeping cultural values alive, which we consider sustainable compromises between heritage and modernization.